The Influence of Supervisor Understanding on IRE Teacher Performance in State JHS in Bone Regency - Agus, Agus; Asnawi, Nur Rahmah; Adam, Adiyana; Swarga, Alim Bubu (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
The purpose of the study is to analyze the ability of the supervisor to understand the Islamic Religion Education (IRE) learning process of State Junior High School (State JHS) in Bone Regency, teacher’s performance, and the influence between these two. The research design used is correlational with the analysis techniques used are descriptive and inferential statistics such as percentage formulation, product-moment correlation coefficient, regression, and coefficient of determination. The sample used in this study was 77 teachers from a population of 154 teachers. The instruments used were questionnaires and interview guides. The results showed that the supervisor’s ability to understand the learning process of IRE in State JHS in Bone Regency was categorized as good with a score of 68%. Teacher performance in the IRE learning process is also categorized as good with a score of 84%. In addition, the supervisor’s ability to understand the learning process has a direct influence on teacher performance in the learning process with a percentage of 37%.